Tea Polyphenols Mitigate Radiation-Induced Ferroptosis and Intestinal Injury by Targeting the Nrf2/HO-1/GPX4 Signaling Pathway - Runtian Li; Lintao Li; Haiyang Wu; Hui Gan; Zhuona Wu; Ruolan Gu; Xiaoxia Zhu; Shuchen Liu; Zhiyun Meng; Guifang Dou (Antioxidants)
Radiation-induced intestinal injury (RIII) is a significant concern for cancer patients receiving radiation therapy, as it can lead to complications such as radiation enteropathy. Presently, there are limited options for preventing or treating RIII. Tea polyphenols (TP), found in tea, provide various health benefits, but their antiradiation mechanisms are not fully understood. C57BL/6 mice pre-treated with TP for five days showed a significant improvement in survival rates after being exposed to 10 Gy of 60Co radiation. In the same way, abdominal exposure to 15 Gy of 60Co radiation effectively mitigated radiation-induced colon shortening, damage to intestinal tissues, oxidative stress, the release of inflammatory factors, and disruptions in intestinal microbial balance. In addition, TP treatment lowered the elevation of reactive oxygen species (ROS), iron imbalance, mitochondrial damage, and ferroptosis in IEC-6 cells post-irradiation. Utilizing network pharmacology, molecular docking, and affinity testing, we identified that TP has the capability to target the Nrf2/HO-1/GPX4 signaling pathway, while EGCG, a principal constituent of TP, interacts with HSP90 and mitigates radiation-induced ferroptosis. These findings suggest that TP may serve as a promising therapeutic agent to alleviate radiation-induced intestinal injury (RII).